Pediatric pulmonary hypertension: insulin-like growth factor-binding protein 2 is a novel marker associated with disease severity and survival - Griffiths, Megan; Yang, Jun; Nies, Melanie; Vaidya, Dhananjay; Brandal, Stephanie; Williams, Monica; Matsui, Elizabeth C.; Grant, Torie; Damico, Rachel; Ivy, Dunbar; Austin, Eric D.; Nichols, William C.; et al. (Pediatric research, 2020)
Background Insulin-like growth factors (IGFs), and their binding proteins (IGFBPs), play a significant role in cardiovascular function and may influence the pathobiology of PAH. We determined the diagnostic and prognostic value of IGF1 and IGFBP2 in pediatric PAH. Methods Serum was analyzed by ELISA for IGF1 and IGFBP2 in pediatric PAH subjects from the NHLBI PAH Biobank (PAHB, n = 175) and a cohort of asthmatic subjects ( n = 46, age 0–21 years) as a chronic pediatric pulmonary disease control. Biomarkers were analyzed with demographic and clinical variables for PAH severity. Results Serum IGF1 was significantly lower in PAH compared to controls, while IGFBP2 was elevated in PAH subjects compared to controls. In the PAHB, IGF1 was negatively associated with mPAP and PVR, while IGFBP2 was positively associated with PVR and negatively associated with cardiac output and 6-min walk distance. Higher IGFBP2 levels were associated with use of prostacyclin therapy. IGFBP2 was associated with death, transplant, or palliative shunt with a Cox proportional hazard ratio of 8.8 ( p < 0.001) but not IGF1 ( p = 0.13). Conclusions Circulating IGFBP2 is a novel marker for pediatric PAH, which is associated with worse functional status, and survival. IGF axis dysregulation may be an important mechanistic target in pediatric pulmonary arterial hypertension. Impact Pediatric pulmonary hypertension is a severe disease, with poorly understood pathobiology. There are few studies looking at the pathobiology of pulmonary hypertension only in children. The IGF axis is dysregulated in pediatric pulmonary arterial hypertension. IGF axis dysregulation, with increased IGFBP2, is associated with worse clinical outcomes in pediatric pulmonary artery hypertension. IGF axis dysregulation gives new insight into the disease process and may be a mechanistic or therapeutic target.